Peningkatan Kualitas Produk UMKM Salikopreneur Menuju Ekonomi Digital - Asmar Yulastri; Ganefri Ganefri; Elfizon Elfizon (Universitas Negeri Padang, 2023)
MSMEs engaged in embroidery, embroidery and clothing craftsmen have limitations in improving the quality of the products produced amidst intense competition with similar products. High quality products follow the wishes of the global market with designs that meet the desires of global market consumers with patterns, colors, aesthetics and high quality material quality that must be met by craftsmen. So far, the quality of the products produced is still the local market standard with low prices because they do not have the ability to produce products with global (international) market quality. The limited ability of partners to produce high-quality products to reach the global market which can be achieved through digital markets must be overcome by conducting training and coaching to partners on production capabilities so that they are able to provide products with timely production in the targeted quantity without neglecting product quality. This PKM service is carried out to solve problems faced by partners in the aspect of developing the quality of embroidery, embroidery and clothing; the problem of product innovation in design adjusting to global market interests with quality products according to global market trends with timely production so as to produce products with the appropriate quality and quantity.